DESIGNING MICROSERVICES ARCHITECTURE FOR SOFTWARE PRODUCT IN STARTUP - Muhammad Rikza Nashrulloh; Ridwan Setiawan; Deni Heryanto; Ade Sutedi; Rickard Elsen (Jurnal Teknik Informatika (Jutif), 2022)
Digital technologies in the world continue to develop in various sectors. This happens not only in developed countries, but also in developing countries such as Indonesia. A trend that continues to develop in the world of information technology becomes a consideration when starting a start-up company. In order to anticipate changes and developments in this trend, it is not uncommon for problems to arise that can directly affect the quality of service for startups. Therefore, a startup needs to create a dynamic culture and infrastructure for the introduction of new technologies. The problems start when startups mature, with more teams, more complex systems, and more traffic to websites or apps. At this stage, startups usually start thinking about scalability issues. to avoid problems, a startup must develop the right architecture for a software product, and a microservices architecture can be a solution to problems. A microservices architecture is an architectural style that structures an application as a collection of small self-contained services modeled around a business domain. This chapter describes the design of microservices architecture for software product in Startup Using Web Service Implementation Methodology .